Convolution method and informativity of recognition space - Mazurov , Vl. D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We give a short survey of application of linear inequalities, in particular of Chernikov’s convolution method, to various problems of pattern recognition, estimation of the informativeness of spaces of the test description of the classification objects, etc.